Senam Kaki Diabetes Melitus untuk Pencegahan Luka Kaki Diabetes Melitus di Ruang Melati Barat RSUD dr Soehadi Prijonegoro Sragen - Eka Lusia; Budi Larasati; Cahya Sulistyo Putri; Irma Mustika Sari; Kushariati Kushariati (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2024)
Background: Diabetes mellitus is a metabolic disorder that causes an increase in blood glucose levels and can trigger chronic complications in various organs. Diabetic foot exercises are an exercise method carried out by diabetes mellitus sufferers to improve foot health. Goal: foot exercises for DM sufferers are to improve blood circulation, especially in the foot area, apart from strengthening the muscles and small nerves in the feet and preventing complications of diabetic feet, such as blood vessel disorders, open wounds. Method: The method for implementing health education is in the form of pre and post tests, then presentation of material using leaflets as well as demonstrations of foot exercises to prevent diabetes mellitus wounds. By delivering it via leaflets and demonstrations, it is hoped that the entire audience can understand and convey it well. Conclusion: Of the 15 audience members present, all of them understood the education about diabetes mellitus foot exercises which can increase knowledge in preventing foot wounds in diabetes sufferers.